Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan serta Dampaknya pada Kepuasan Kerja Karyawan PT Jasa Marga (Persero) Kantor Cabang Surabaya - Kurniawati, Elya; Troena, Eka Afnan (Jurnal Aplikasi Manajemen, 2013)
Service industry has an important role in the economical aspects of every country. In the most competitive era like today, the key to survival and success is providing a quality service. The strict competitiveness causes many companies to focus on their customer satisfaction. The major factor which determines customer satisfaction in service industry is employees' behaviour which relates directly to the customers. Taking this as their consideration, PT Jasa Marga (Persero) put giving the best service as their principal. Many organization leader believe that customer satisfaction is based on satisfied employees' service.This research aims to examine the influence of leadership style and organisation culture to employees'performance and its impact on employees'satisfaction. The research data indicated that: (1) leadership style gives significant influence to employee job satisfaction, (2) organizational culture gives significant influence to employees job satisfaction, (3) leadership style gives indirect influence to employee job satisfaction through employee performance, (4) organizational culture influence to employee job satisfaction indirectly through employee performance, (5) leadership style and organizational culture give influence to employee job satisfaction through employee performance.